2013
DOI: 10.1089/pop.2012.0087
|View full text |Cite
|
Sign up to set email alerts
|

Turning Readmission Reduction Policies into Results: Some Lessons from a Multistate Initiative to Reduce Readmissions

Abstract: Efforts are under way nationally to reduce avoidable hospital readmissions by changing payments to hospitals, but it is unclear how well or how quickly these policy changes will produce widespread reductions in hospital readmissions. To examine some of the challenges to implementing such approaches, the authors analyzed the early experiences of 3 statewide programs to reduce preventable readmissions that began in 2009. Based on interviews with program participants in 2011, the authors identified 3 key obstacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Consistent with other studies (Gerhardt et al, 2013), we found a decline in hospital readmissions for Medicare beneficiaries from 2008 to 2012, but these declines were not significantly greater in AF4Q communities. Our findings are aligned with the null findings of other large interventions to reduce readmissions, including evaluations of the STate Action on Avoidable Hospitalizations (STAAR) (Boutwell et al, 2011;Mittler et al, 2013) ,.0001…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with other studies (Gerhardt et al, 2013), we found a decline in hospital readmissions for Medicare beneficiaries from 2008 to 2012, but these declines were not significantly greater in AF4Q communities. Our findings are aligned with the null findings of other large interventions to reduce readmissions, including evaluations of the STate Action on Avoidable Hospitalizations (STAAR) (Boutwell et al, 2011;Mittler et al, 2013) ,.0001…”
Section: Discussionsupporting
confidence: 78%
“…Alliances may not have had the capacity to focus on readmissions to the same degree as other communities that did not participate in AF4Q. Although non-AF4Q communities working to reduce readmissions often had narrow mandates (e.g., STAAR [Boutwell et al, 2011;Mittler et al, 2013] and CCTP [Econometrica, 2014]), AF4Q communities were charged with improving quality across several domains. Reducing readmissions in non-AF4Q communities may have also been a high priority, given the public reporting and financial penalties associated with readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing readmissions must be followed up with post-discharge and community-based care interventions that can improve, as well as sustain, the health of the population to decrease hospital returns. While several interventions have been developed that aim to reduce unnecessary readmissions by improving the transition of care process during and post-discharge [13-17], there is a lack of evidence on what interventions are most effective with readmission reductions on a broad scale [18]. …”
Section: Introductionmentioning
confidence: 99%
“…5 However, these QI strategies lack evidence applicable to all health care settings. 11 There is a call for caution regarding the speed of change and innovation because evidence is lacking that certain strategies work in all cultures and processes. 11 A process that worked in one system may not be applicable to another.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building new infrastructure and instituting policies that work within one particular health care system are costly and time consuming and require building collaborative relationships across all health care settings before consistent cost-savings strategies have been proven efficacious. 11 The QI process that is the focus of this project considered PC consults as a resource to address PPRs. The number of US hospitals offering PC services has been growing rapidly for more than a decade.…”
Section: Literature Reviewmentioning
confidence: 99%